Charismatic Leadership of School Principals: Systematic Literature Review Analysis - Ayu Lestari; Ferry Heryadi; Iswahyu Pranawukir; Samuel PD Anantadjaya; Afif Alfiyanto (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
Charismatic leadership has been a significant focus of research in the educational leadership literature, especially in the context of school principals. This article presents a systematic analysis of the concept of charismatic leadership, its implications, and its impact on the school environment. Through qualitative methods using literature analysis, we identify traits, impacts, and strategies of charismatic leadership. The findings show that charismatic principals have a strong vision, practical communication skills, high self-confidence, empathy, and personal influence that positively influence the attitudes and behaviours of staff and students. The impact includes increased motivation, academic performance, and a positive school culture, with strategies such as developing a solid vision, building trust, empowering staff, participation in decision-making, and being a role model. These findings provide an in-depth understanding of the role of charismatic leadership in improving the quality of education and creating supportive learning environments. Practical implications include the development of leadership training programs and a better understanding for education policymakers of the importance of charismatic characteristics in school leadership. This research fills a gap in the literature by highlighting the critical role of charismatic leadership in educational contexts, particularly in developing countries, as well as emphasizing the need for more research involving the perspectives of teachers and school staff.